2004
DOI: 10.1182/blood-2004-02-0631
|View full text |Cite
|
Sign up to set email alerts
|

Kit and FcϵRI mediate unique and convergent signals for release of inflammatory mediators from human mast cells

Abstract: In human mast cells, derived from CD34 ؉ peripheral blood cells, we observed that Kit ligand (KL) failed to induce degranulation but acted in synergy with antigen to markedly enhance degranulation, levels of cytokine gene transcripts, and production of cytokines. Further examination revealed that antigen and KL activated common and unique signaling pathways to account for these varied responses. KL, unlike antigen, failed to activate protein kinase C but activated phospholipase C␥ and calcium mobilization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
157
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 66 publications
12
157
0
2
Order By: Relevance
“…In this study, we found that Rcan1 deficiency does not impose upon the activation of the MAPK family members JNK, p38, and ERK, nor does it impact upon Akt/PI3K-signaling activity (41). These results are consistent with a previous report showing that cyclosporine A had no effect on SCF-mediated JNK and p38 (40).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that Rcan1 deficiency does not impose upon the activation of the MAPK family members JNK, p38, and ERK, nor does it impact upon Akt/PI3K-signaling activity (41). These results are consistent with a previous report showing that cyclosporine A had no effect on SCF-mediated JNK and p38 (40).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to murine mast cells, antigen was not able to induce STAT5 phosphorylation in human mast cells (18). This discrepancy probably reflects different signaling pathways in human and murine mast cells.…”
mentioning
confidence: 75%
“…Traditionally, analysis of signaling in human basophils and mast cells has been performed using Western blot techniques (18,25). Recently, it has been demonstrated that flow cytometry can generate qualitative results concerning dose responses and kinetics of signaling molecules similar and complementary to the data obtained with blotting techniques (19,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in mast cell deficient KIT-mutant, W/W v , W/W sh , and SCF-mutant, Sl/Sl d , mice, signaling through KIT is crucial for correct development, growth, differentiation, survival, and homing of mast cells [33]. Consistently, in in vitro studies with both human and mouse mast cells, KIT activation is not abled by itself to induce mast cell degranulation, but can enhance mast cell degranulation and cytokine production in combination with antigenic stimulation [34,35]. In contrast to FcεRI, KIT is a single chain receptor with intrinsic tyrosine kinase activity, although it shares downstream signaling proteins in common with the FcεRI-dependent cascade.…”
Section: Kit Enhances Fcεri-mediated Activationmentioning
confidence: 99%